Albumin/vaccine nanocomplexes that assemble in vivo for combination cancer immunotherapy. Issue 1 (December 2017) - Zhu, Guizhi; Lynn, Geoffrey; Jacobson, Orit; Chen, Kai; Liu, Yi; Zhang, Huimin; Ma, Ying; Zhang, Fuwu; Tian, Rui; Ni, Qianqian; Cheng, Siyuan; Wang, Zhantong; et al.
Abstract Subunit vaccines have been investigated in over 1000 clinical trials of cancer immunotherapy, but have shown limited efficacy. Nanovaccines may improve efficacy but have rarely been clinically translated. By conjugating molecular vaccines with Evans blue (EB) into albumin-binding vaccines (AlbiVax), here we develop clinically promising albumin/AlbiVax nanocomplexes that self-assemble in vivo from AlbiVax and endogenous albumin for efficient vaccine delivery and potent cancer immunotherapy. PET pharmacoimaging, super-resolution microscopies, and flow cytometry reveal almost 100-fold more efficient co-delivery of CpG and antigens (Ags) to lymph nodes (LNs) by albumin/AlbiVax than benchmark incomplete Freund's adjuvant (IFA). Albumin/AlbiVax elicits 10 times more frequent peripheral antigen-specific CD8+ cytotoxic T lymphocytes with immune memory than IFA-emulsifying vaccines. Albumin/AlbiVax specifically inhibits progression of established primary or metastatic EG7.OVA, B16F10, and MC38 tumors; combination with anti-PD-1 and/or Abraxane further potentiates immunotherapy and eradicates most MC38 tumors. Albumin/AlbiVax nanocomplexes are thus a robust platform for combination cancer immunotherapy. Albumin conjugates can enhance drug delivery. Here, the authors repurpose albumin-binding Evans blue to develop nanovaccines that co-deliver adjuvants and tumor neoantigens to antigen-presenting cells in lymph nodes, resulting in potent and durable antitumour immunity in combination immunotherapy.